Anacardato de cálcio e sua associação com ácido cítrico na ração para matrizes de codornas de corte - Silva, Cleane Pinho da (2019)
In order to evaluate the effects of the use of calcium anacardate (CAC), as a source of anacardic acid, in diets for breeding quails and its association with citric acid (CA), 540 European quails at 21 weeks of age were used. The birds were housed in laying cages and following a completely randomized design, with nine treatments and six replications of ten birds, with the experimental unit consisting of eight females and two males. The treatments consisted of diets being: T1 - diets without adding acids; T2 - feed with addition of 0.25% of CA; T3 - feed with 0.25% CA to 0.25% CA; T4 - feed with 0.50% CA; T5 - feed with 0.50% CA associated with 0.25% CA; T6 - feed with 0.50% CA associated with 0.50% CA; T7 - feed with 0.75% CAC; T8 - feed with 0.75% CA associated with 0.25% CA; T9 - feed with 0.75% CA associated with 0.50% CA. The experimental period was 210 days divided into 10 periods lasting 21 days each, in which the performance of the matrices, egg quality, incubation parameters and the performance of the progeny were evaluated. However, for the quality of the eggs, there was a significant effect only on the lipid oxidation of the yolk, obtaining less oxidation for the egg yolks of the birds fed with diets containing: 0.50% of CAC associated with 0.25% of CA; 0.50% CAC associated with 0.50% CA and 0.75% CAC, when compared to the control group. It was concluded that the inclusion of calcium anacardate and its association with citric acid in the diet for meat type quails has no influence on the parameters of bird performance, incubation, progeny performance and egg quality except for lipid oxidation of the yolk , and 0.75% CAC or 0.50% CAC can be included in association with 0.25% CA in the feed to obtain less oxidation